English for Specific Purposes (ESP) Materials Based on Needs Analysis for Nursing Students in Facing the Society 5.0 Era - Yuriatson Jubhari; Nurliah; Awalia Aziz; Afif Zuhdy Idham; Abd. Rajab (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2024)
The notion of Needs analysis has evolved over the decades. Currently, the process of requirements analysis has become significantly more comprehensive. Its purpose is to gather information about the learners and to establish the desired learning setting and atmosphere for studying English for Specific Purposes (ESP). This study was conducted in Politeknik Sandi Karsa. There were 23 students in nursing study program. The researcher provides a set of 12 themes, all of which received a consistently high ranking from all types of respondents as suitable learning material. The findings of this study are anticipated to serve as a point of reference for future research, namely in the areas of syllabus/RPS preparation and the development of English teaching materials for nursing students. There are numerous crucial factors that may be utilized as a valuable reference in the development of ESP materials for the sub-skills of speaking, listening, reading, and writing. It can be concluded that the majority of students prioritize the development of vocabulary and speaking skills over other skills due to their aspiration to work as a nurse abroad for nursing students at Politeknik Sandi Karsa Makassar Indonesia.